2014
DOI: 10.1186/1471-244x-14-71
|View full text |Cite
|
Sign up to set email alerts
|

The Chinese version of story recall: a useful screening tool for mild cognitive impairment and Alzheimer’s disease in the elderly

Abstract: BackgroundDecline in verbal episodic memory is a core feature of amnestic mild cognitive impairment (aMCI). The delayed story recall (DSR) test from the Adult Memory and Information Processing Battery (AMIPB) discriminates MCI from normal aging and predicts its conversion to Alzheimer’s dementia. However, there is no study that validates the Chinese version of the DSR and reports cut-off scores in the Chinese population.MethodsA total of 631 subjects were screened in the memory clinics of Dongzhimen Hospital, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…According to the regression models for immediate and delayed recall scores, results demonstrated that age and education were negatively and positively correlated, respectively, which are according to the literature (Shi et al, 2014). Gender also proved to have an effect on two LM scores, as women scored higher than men.…”
Section: Discussionsupporting
confidence: 52%
“…According to the regression models for immediate and delayed recall scores, results demonstrated that age and education were negatively and positively correlated, respectively, which are according to the literature (Shi et al, 2014). Gender also proved to have an effect on two LM scores, as women scored higher than men.…”
Section: Discussionsupporting
confidence: 52%
“…Secondary outcome measures included changes from baseline to 52 weeks in the MMSE scores (ranging from 0 to 30) [12], AMIPB‐DSR (scores range from 0 to 56) [11], and ADCS‐ADL‐MCI‐24 items (scores range from 0 to 69), with lower scores indicating worse function [14].In addition, the changes in the deficiency of kidney essence using Clinical Global Impression of Change of Kidney Deficiency (CGIC‐KDS) was assessed [18]. CGIC‐KDS, based on information from a semistructured interview with the patient and the legal guardian, was designed specifically to evaluate the global assessment of changes of kidney function deficiency based on clinician and caregiver in TCM.…”
Section: Methodsmentioning
confidence: 99%
“…Amnestic MCI is the main type, approximately 80% of which converted to dementia in a 6-year follow-up (Petersen, 2004). The previous study found delayed story recall (DSR) was a useful tool for differentiating MCI from normal cognition (NC), but not so good for differentiating MCI with dementia (Shi et al, 2014). In addition to memory impairment, recent studies confirmed instrumental activities of daily living (IADL) were also affected in patients with MCI.…”
Section: Introductionmentioning
confidence: 99%